Integrating the Halal Tourism Value Chain into Global Destination Management Frameworks - Voak, Adam; Wahyuni, Hana Catur; Dahlan, Ahmad (Journal of Halal Lifestyle and Sustainability, 2025)
This paper explores current perspectives regarding the Halal Tourism Value Chain (HTVC), a crucial and burgeoning segment in the international tourism sector, focused on fulfilling Muslim travellers' unique requirements. The chain is designed to adhere strictly to Islamic principles, as is required by followers of this faith. The paper offers a comprehensive examination of aspects of the HTVC, discussing the essential components of the chain and identifying all the participants who are involved in providing its essential services. Through a synthesis of the literature, the discussion will elucidate the spectrum of activities involved in the Halal tourism chain, which must be tailored to meet the Muslim demographic’s requirements. The findings highlight the significance of certification bodies, travel agencies, hospitality providers and regulatory frameworks. Furthermore, the study discusses the difficulties encountered within the sector, which relate to market segmentation, cross-cultural sensitivities and certification inconsistencies. The study concludes with strategic recommendations for enhancing the HTVC, emphasising the significance of cooperation between service participants, the importance of technological integration and the development of standard guidelines to ensure a seamless and guaranteed Halal travel experience. This investigation is purposefully designed to provide a meaningful contribution to the HTVC, offering practical insights for industry practitioners aiming to capitalise on this rapidly expanding market.